2023
DOI: 10.1093/jncics/pkad023
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory and insulinemic potential, risk of hepatocellular carcinoma, and chronic liver disease mortality

Abstract: Background Diet modulates inflammation and insulin response and may be an important modifiable factor in the primary prevention of hepatocellular carcinoma (HCC) and chronic liver disease (CLD). We developed the empirical dietary inflammatory pattern (EDIP) and empirical dietary index for hyperinsulinemia (EDIH) scores to assess the inflammatory and insulinemic potentials of diet. Objective We prospectively examined the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Previous studies suggested that several factors including age, sex, race, smoking status, drinking status, marital status, BMI and diabetes could modify the associations between inflammatory dietary pattern and chronic liver diseases (16,(35)(36)(37) . Therefore, we stratified analyses according to these factors and tested the potential interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that several factors including age, sex, race, smoking status, drinking status, marital status, BMI and diabetes could modify the associations between inflammatory dietary pattern and chronic liver diseases (16,(35)(36)(37) . Therefore, we stratified analyses according to these factors and tested the potential interactions.…”
Section: Discussionmentioning
confidence: 99%